Clinical and Epidemiological Characteristics of Leptospirosis in the Gomel Region - O. L. Tumash; L. P. Mamchits (Эпидемиология и вакцинопрофилактика)
Relevance. Leptospirosis is a zoonotic ubiquitous natural focal infectious disease that has an adverse effect on human and pet health. The territory of the Republic of Belarus in terms of its natural-climatic and soil-geographical conditions is favorable for the existence of both natural and anthropurgical foci of leptospirosis. The purpose of the work is to study the long-term dynamics of the incidence of leptospirosis in the population of the Gomel region and the clinical and epidemiological features of leptospirosis. Materials and methods. The material for the study was the data of the state statistical reporting «Report on individual infectious, parasitic diseases and their carriers» for the period from 2002 to 2022. In this work, epidemiological diagnostic methods and statistical research methods were used. Descriptive retrospective continuous study of these case histories of patients diagnosed with Leptospirosis of the Gomel Regional Infectious Diseases Clinical Hospital institution was conducted to describe clinical data. Results. In the period from 2002 to 2022, 161 cases of leptospirosis were registered in the Gomel region with an average incidence rate of 0.52 per 100 thousand population. Over this period of time, the incidence of leptospirosis was characterized by an uneven distribution and was undulating. Periods with a low incidence of 0.14–0.42 cases per 100 thousand population lasting 5-6 years alternated with periods of rising incidence to 0.99 cases per 100 thousand population lasting 3 years. In 2022, a sharp rise in the incidence of leptospirosis in the Gomel region was registered, and therefore 15.8 times higher than the incidence in 2021, the incidence rate was 1.11 per 100 thousand of the population and exceeded the national average by 4.6 times. Adults predominated among the sick (93.3%). At the same time, 73.0% of the patients were urban residents. The source of infection in 81.2% of cases were rodents, in 7.52% of cases domestic animals. In 7.52% of cases, the disease appeared as a result of professional activity, only in 3.76% of cases the disease occurred after swimming in open water. Thus, the main route of transmission of leptospirosis at present is contact (88.72%), alimentary and water are less important, respectively 7.52% and 3.76%. Results of serological examination for leptospirosis by RMA showed that 5 serogroups of leptospir circulate among rodents: L. Pomona and L. Canicola, L. Grippotyphosa, L. Icterohaemorrhagiae, L. A. Ustralis. 36.4% of the samples showed a positive result at the same time to several serogroups. L. Grippotyphosa, L. Cterohaemorrhagiae and L. Pomona were detected more often, in total, these pathogens accounted for 46.5% of positive samples. The results of the survey of farm animals showed that 60.6% of the sera studied had positive results of RMA with leptospirs of several serogroups. L. Sejroe was also isolated – in 12.3% of samples, L. Hebdomad – in 1.3% of samples, L. Icterohaemorrhagiae – in 1.2%, L. Pomona – in 0.3%, others – 24.2%. In the period from 2002 to 2021, the following serogroups were isolated in patients with leptospirosis: L. Grippotyphosa – 36%, L. Pomona and L. Canicola – 16%, L. Australi – 13%, L. Wolffi – 9%, L. Icterohaemorrhagiae – 7% and L. Tarassovi – 3%. In 2022, there is a change in the polytypage of leptospir: L. Icterohaemorrhagiae (6.7%), L. Tarassovi (6.7%), L. Wolffi (6.7%), L. Pomona (13.3), L. Astralis (13.3), L. Canicola (6.7%), 6.7% – L. Sejroe, L. Grippotyphosa Moskva – 40%. For the period from 2005 to 2022, 49 people diagnosed with leptospirosis were treated at the Gomel Regional Infectious Diseases Hospital, of which men accounted for 69%, the average age of patients was 34.5 ± 3.8 years. Most patients are hospitalized on day 6 [4 – 8] of illness. All patients complained of fever, 86% of patients had muscle pain, headaches were recorded in 56.0%, yellowing of the skin and sclera – 34.0%, abdominal pain – 38%, 25% of patients reported nausea, vomiting, diarrhea syndrome. 28.6% of patients had an icteric form of leptospirosis, Weil's syndrome was diagnosed in 9.3% of patients, hemorrhagic syndrome was observed in 18.7% of patients. All patients had laboratory confirmation of the diagnosis. The duration of hospitalization was 15 [9 – 23] days. 1 case of the disease ended with a detailed outcome for the entire observation period. Conclusion. The incidence of leptospirosis in the Gomel region is undulating and is characterized by a change in periods of rising incidence lasting up to 3 years with periods of low incidence lasting up to 5 years. The results of the study suggest that the emergence and spread of the leptospira serotype in the territory led to a new increase in the incidence. Thus, continuous qualitative monitoring of leptospira serotypes among the population of sources of infection should be carried out.